Early Organizational Diffusion of Contemporary Policies: Narratives of Sustainability and Talent Management. (1st December 2015) - Pinnington, Ashly; Alshamsi, Abdullah; Karatas-Ozkan, Mine; Nicolopoulou, Katerina; Ozbilgin, Mustafa; Tatli, Ahu; Vassilopoulou, Joana
Abstract: The early stages of organizational diffusion of contemporary policies that were institutionalized elsewhere often presents managers and employees with the need to adopt new work practices and ways of understanding. This study examines well-formed and incomplete employee narratives of sustainability and talent management. We discuss and then conclude on how non-standardized and even confused narratives can be illuminating for understanding the early diffusion of institutions and innovations in organizations.